Influence of the Changes of the Structure of Foundry Bentonites on Their Binding Properties - Sylwia ŻYMANKOWSKA-KUMON; Mariusz HOLTZER; Ewa OLEJNIK; Artur BOBROWSKI (Medžiagotyra, 2012)
In this paper, the effects of the examination of the structure of calcium bentonites, activated by sodium carbonate, applied in the foundry industry as a binding agent for moulding sands, subjected to the effects of high temperature, were presented. The examination was conducted with the use of the infrared spectroscopy (FTIR) and X-ray analysis (XRD). In addition, the montmorillonite contents in the bentonite sample was determined with the use of the modern, Cu(II)-TET complex method and the technological properties of moulding sands containing the examined bentonites, such as: compactability, permeability, compression strength were examined. DOI: http://dx.doi.org/10.5755/j01.ms.18.1.1342